Multidrug resistance 1 gene transfer can confer chemoprotection to human peripheral blood progenitor cells engrafted in immunodeficient mice - Schiedlmeier, Bernhard; Schilz, Andrea J.; Kühlcke, Klaus; Maier-Laufs, Stephanie; Baum, Christopher; Zeller, W. Jens; Eckert, Hans-Georg; Frühauf, Stefan (Human gene therapy, 2002)
Myelosuppression is the main side effect of cancer chemotherapy. An improved rate of retroviral vector-mediated gene transfer to hematopoietic stem cells, shown in more recent clinical trials, has created the basis to test the concept of myeloprotective gene therapy. We transplanted clinical-scale human peripheral blood progenitor cell grafts (n = 2) transduced with retroviral vector SF91m3, which contains the human multidrug resistance 1 gene (MDR1), into nonobese diabetic/severe combined immunodeficient (NOD/SCID) mice. Engrafted mice of one cohort were protected from paclitaxel toxicity (p < 0.05) and we noted a similar trend in the second cohort. In paclitaxel-treated mice that had received gene-transduced cells we found a significant increase in gene marking (p < 0.05 - p < 0.01) or P-glycoprotein expression (p < 0.01) compared with their chemotherapy-naive counterparts. This is the first report showing that cytostatic drug resistance gene therapy can mediate chemoprotection of human clinically relevant stem cell populations with marrow engraftment potential.
Gesehen am 20.01.2022